2021
DOI: 10.1186/s40834-021-00165-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with modern contraceptive use among women with no fertility intention in sub-Saharan Africa: evidence from cross-sectional surveys of 29 countries

Abstract: Background In sub-Saharan Africa, the majority of women of reproductive age who want to avoid pregnancy do not use any method of contraception. This study sought to determine the factors associated with  modern contraceptive use among women with no fertility intention in sub-Saharan Africa. Methods This study used data from the Demographic and Health Surveys of 29 countries in sub-Saharan Africa. A total of 87,554 women aged 15–49 with no fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
76
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 34 publications
4
76
2
1
Order By: Relevance
“…15 The contraceptive prevalence rate among married women in sub-Saharan Africa increased from 14.7% in 2000 to 27.9% in 2019 and 29.6% in 2021. 16,17 In the past decades, studies in developing countries have shown that contraceptive use is influenced by various factors; these factors include demographic characteristics, religious beliefs, knowledge of contraception, education of couples, gender preference among children, the quality of the Contraception among women, limited choice of methods, and fear or experience of side-effects. 6,11,[18][19][20][21][22][23][24] The unmet need for modern contraception is high in Liberia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The contraceptive prevalence rate among married women in sub-Saharan Africa increased from 14.7% in 2000 to 27.9% in 2019 and 29.6% in 2021. 16,17 In the past decades, studies in developing countries have shown that contraceptive use is influenced by various factors; these factors include demographic characteristics, religious beliefs, knowledge of contraception, education of couples, gender preference among children, the quality of the Contraception among women, limited choice of methods, and fear or experience of side-effects. 6,11,[18][19][20][21][22][23][24] The unmet need for modern contraception is high in Liberia.…”
Section: Introductionmentioning
confidence: 99%
“…27 Modern contraceptive is an important and cost-effective public health intervention to reduce maternal mortality and avert unintended pregnancies, especially in developing countries. 13,17,28 However, mCPR was low in most of the developing countries, including Liberia. 7,27,29 To increase the level of contraceptive use, it is necessary to understand factors that significantly influence contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa will account for the majority of global population growth in the coming decades, while many other regions will begin to see population decline. Between 2019 and 2050, the global population is expected to grow by almost two billion people, with 1.05 billion (52%) of that growth occurring in Sub-Saharan African countries [ 1 ]. Ethiopia is the most populous country in Sub-Saharan Africa, with a population of 112 million people and a fertility rate of 4.6 children per woman.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evidence from studies done in Sub Saharan Africa, western Africa, D.R Congo and Nigeria reported that urban women use modern contraception more frequently than rural women (1,15,16), and rural fertility is significantly higher than urban fertility (1).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Sierra Leone using the 2013 demographic health survey (DHS) data found that living in an urban area was associated with increased odds of modern contraceptive utilization among married or in-union women when compared to living in rural areas (14). Additionally, evidence from studies done in Sub Saharan Africa, western Africa, D.R Congo and Nigeria reported that urban women use modern contraception more frequently than rural women (1, 15, 16), and rural fertility is significantly higher than urban fertility (1).…”
Section: Introductionmentioning
confidence: 99%